The Most Current Problems in Teaching the Subject of Life Safety - Tursunova Elza Akramovna; Kotova Lyubov Valentinovna (European Journal of Life Safety and Stability (2660-9630), 2022)
The article highlights and characterizes the main problems of teaching BJD in a university at the current level of education development. The new generation poses important and serious tasks for the teachers of the Belarusian Railway to provide advanced high-quality education for students.